Micro-scale voltaic cell experiment based on PjBLSTEM using POME waste for sustainable energy education - Hanif, Nayudin; Louise, Isana Supiah Yosephine; Suyanta (Academica Press Solutions, 2025)
This study explores the utilization of Palm Oil Mill Effluent (POME) as an electrolyte in a micro-scale voltaic cell experiment integrated into a Project-Based Learning–Science, Technology, Engineering, and Mathematics (PjBL-STEM) framework. The primary aim is to develop an applicable green chemistry learning model that contributes to sustainable energy solutions. A quasi-experimental method was implemented with Grade XI science students at Sekolah Indonesia Kota Kinabalu, involving the stages of problem identification, experimental design, implementation, data analysis, and reflection. Results demonstrate that POME effectively functions as an alternative electrolyte, producing up to 8.71 Volts and 3.12 mA of current in a five-cell series configuration. The linear relationship between the number of POME cells and the generated voltage (Y = 17.25X + 1.85) indicates its potential as a micro-energy source for low-power electronic devices. The integration of local waste into science education not only supports the achievement of Sustainable Development Goals (SDGs) No. 7 (Affordable and Clean Energy) and No. 12 (Responsible Consumption and Production), but also fosters opportunities for renewable energy innovation grounded in local contexts. This model can be adapted in resource-limited schools to promote learning that is relevant, contextual, and environmentally conscious.